Literatura y “contra-historia”: los discursos del origen en Yo el Supremo y Moi, Toussaint Louverture - Javier Uriarte (Les Cahiers ALHIM)
This article seeks to discuss the ways in which two key Latin American emancipatory processes have been re-interpreted in two novels: Augusto Roa Bastos’ Yo el Supremo (1974) and Jean-Claude Fignolé’s Moi, Toussaint Louverture, avec la plume complice de l’auteur (2004). These texts revisit Paraguayan and Haitian history respectively and suggest new readings of the national hero and the origins of the nation. They propose the ambivalence and contradictions of their protagonists as necessary elements to re-think the nation. I believe it is necessary and even –after the recent and devastating earthquake in Haiti– urgent to consider the emancipatory process in Latin American from the perspective of the Paraguayan and Haitian independences. The adoption of this perspective allows us to re-signifiy the Bicentenary of Independence and problematize Latin American history in new ways. By making explicit these similarities between two narrative projects that seek to re-read (and re-write) the foundational processes in their respective countries, I intend to establish a dialogue between two process of Independence that, although having been undoubtedly key to the understanding of the history of independent Latin America, have been drastically silenced. In this sense, this essay seeks to make a strong argument for the consideration of Haiti as a part of Latin America.